Studies of in vitro propagation of Rhynchostylis retusa – promising foxtail orchid - Kaur, Kirandeep (My University, 2019)
A simple and efficient shoot organogenesis protocol was developed from leaf explants of Rhynchostylis retusa. Initially, the protocorm-like bodies (PLB) culture was established using seeds of the plant. The surface disinfected seeds of R. retusa were cultured on basal MS medium to attain maximum number of PLBs per seed. However, the established PLB cultures were found to be devoid of any leaves which limits the regeneration studies, thus attempts were made to attain desired leaf growth from the cultures. For this purpose, PLBs were cultured on different concentration and combinations of PGRs (BA, NAA and GA3). Among various combinations tested, MS medium fortified with 2.5 μM NAA, 1μM BA and 1μM GA3 was found to be optimum for leaf growth from PLB clumps. These leaf explants were used to induce shoot organogenesis on MS medium variously supplemented with BA, NAA, IAA and 2,4-D. Maximum number of shoot buds were induced on MS medium supplemented with 2.5 μM BA after 28 days of the culture. It was important to note that any of the auxin was not able to induce shoot organogenesis in the explants except NAA (2.5 – 5.0 μM). The pathway of regeneration was also confirmed through histological studies which revealed that shoot buds differentiate from the leaf samples through intermediate callus phase. Further, clonal uniformity was analysed through Random amplified polymorphic DNA and Inter simple sequence repeat markers and the regenerated shoots found true to type. Further, the PLBs were encapsulated in alginate matrix and effect of storage temperature and period on synthetic seeds viability was evaluated. The synthetic seed germination potential was found to decline with increasing storage period. Storage at 4 °C showed survival for a period of 60 days while synthetic seeds stored at 25 °C resulted in rapid deterioration before 60 days. This indicated that storage at lower temperature is more effective for synthetic seed germination.
Keywords: Artificial seeds; Plant growth regulators; Protocorm like bodies; RAPD